HUBUNGAN ADVERSITY QUOTIENT DENGAN TINGKAT STRES AKADEMIK PADA DOKTER MUDA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Saphira Adriyan Putri; Zulharman "; Firdaus " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTEach individual must have experienced stress including clerkship. Therefore, the individual must have the ability to manage stress. The stress level on each individual is influenced by many factors, one of the factors is adversity quotient. The high adversity quotient is able to help somebody to manage and deal with the stress. The purpose of this study was to determine the relationship between adversity quotient and academic stress level in clerkship of Riau University. Cross-sectional analytic correlative study designed to 145 medical students who selected by minimal sample which will be divided every station with proportional random sample. Collecting data used adversity quotient questionnaire based on the theory of Paul G Stoltz and Medical Student Stressor Questionnaire (MSSQ) using an online questionnaire (google docs). Data was analyzed bivariate by Spearman correlation. The result of this study was moderate negative correlation between adversity quotient and academic stress level in clerkship of Riau University with r = -0,558, r square = 0,311 and p value = 0,000.Keywords: academic stress level, adversity quotient, clerkship